Peluang Dan Tantangan Perencanaan Pembentukan Koperasi Mitra Gojek di Era Milenial - Nurhayat Indra; Mardiyah, Tusholihah; Ajeng, Setianingsih; Desi, Lusiana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
This scientific paper is entitled Opportunities and Challenges for the Establishment ofGojek Partner Cooperatives in the Millennial Era. The writing of this paper discussesthe current condition of cooperatives and the very rapid growth of millennialgeneration, as well as the opportunities and challenges of forming cooperatives in themillennial era. This scientific paper uses qualitative research methods, where the dataobtained comes from observations, distributing questionnaires to related parties,reading and studying the existing literature, and browsing to various websites to getinformation in accordance with the research conducted. This scientific paper aims tofind out how to find out the condition of cooperatives in the West Java region, to findout the response of Gojek partners in responding to Gojek cooperatives, to how to forma Gojek partner cooperatives, to find out opportunities and challenges in planning theestablishment of Gojek partner cooperatives.